Anxiety levels in "Under 18" and "Under 20" Elite Rugby Players of National Teams in different field positions (Niveles de ansiedad en jugadores de Elite de equipos de Rugby "Sub-18" y “Sub-20" en diferentes posiciones de campo) - Batista, Marco; Catarino, Jose; Fernandes, Helder; Vaz, Luis; Serrano, João; Honório, Samuel (Retos, 2019)
Abstract. The objective of this study was to encourage Rugby players to promote abilities in this sport, therefore we have evaluated the somatic anxiety, cognitive anxiety and self-confidence values of U18 and U20 rugby athletes of the Portuguese Nationals Rugby Teams, who participated respectively in the U18 Elite European Championship and in the U20 Trophy World Rugby, comparing forwards and defenders. For data collection, we used the CSAI-2 which assesses cognitive anxiety, somatic anxiety and self-confidence. The results showed more favourable average parameters for the group of athletes U20. However, there were only significant differences favourable to the U20 team in the domain of self-confidence, in a general level between teams and in the forward positions. Resumen. El objetivo de este estudio fue animar a los jugadores de rugby para promover las habilidades en este deporte, la evaluación de la ansiedad somática, ansiedad cognitiva y la autoconfianza de los atletas de rugby Sub 18 y Sub 20 de los equipos nacionales de rugby portugués que participó, respectivamente, en U18 European Elite Campeonato y en el U20 Trophy World Rugby, comparando avanzados y defensas. Para la recolección de datos, utilizamos el CSAI-2 que evalúa la ansiedad cognitiva, la ansiedad somática y la autoconfianza. Los resultados mostraron parámetros medios más favorables para el grupo de atletas Sub-20. Sin embargo, sólo hubo diferencias significativas favorables para el equipo Sub-20 en el dominio de la autoconfianza, en un nivel general entre equipos y en las posiciones de avanzados.